2011
DOI: 10.1158/0008-5472.can-11-1161
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Glycosylating Enzyme GALNT2 Regulates the Malignant Character of Hepatocellular Carcinoma by Modifying the EGF Receptor

Abstract: Extracellular glycosylation is a critical determinant of malignant character. Here, we report that N-acetylgalactosaminyltransferase 2 (GALNT2), the enzyme that mediates the initial step of mucin type-O glycosylation, is a critical mediator of malignant character in hepatocellular carcinoma (HCC) that acts by modifying the activity of the epidermal growth factor receptor (EGFR). GALNT2 mRNA and protein were downregulated frequently in HCC tumors where these events were associated with vascular invasion and rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 31 publications
3
88
1
Order By: Relevance
“…However, glycogenes responsible for these O-glycans and their functions in hepatocellular carcinoma remain largely unknown. Previously, we reported that GALNT1 and GALNT2 are the major GalNAc transferases in liver tissues and that GALNT2 modulates the sialyl Tn expression on EGF receptor in hepatocellular carcinoma cells and suppresses their malignant properties (18). Here, we further report that C1GALT1 expression is dysregulated in hepatocellular carcinoma and C1GALT1 modulates the expression of mucin-type O-glycans on hepatocellular carcinoma cell surfaces.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, glycogenes responsible for these O-glycans and their functions in hepatocellular carcinoma remain largely unknown. Previously, we reported that GALNT1 and GALNT2 are the major GalNAc transferases in liver tissues and that GALNT2 modulates the sialyl Tn expression on EGF receptor in hepatocellular carcinoma cells and suppresses their malignant properties (18). Here, we further report that C1GALT1 expression is dysregulated in hepatocellular carcinoma and C1GALT1 modulates the expression of mucin-type O-glycans on hepatocellular carcinoma cell surfaces.…”
Section: Discussionsupporting
confidence: 66%
“…Primers for GAPDH were 5 0 -GACAAGCTTCCCGTTCTCAG-3 0 and 5 0 -ACAGTCAGCCG-CATCTTCTT-3 0 . Quantitative real-time PCRs were carried out as described previously (18).…”
Section: Cdna Synthesis and Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence indicate that changes in O-linked glycans allow neoplastic cells to differentiate, invade, and spread throughout the organism (20,21). The alteration of O-glycans attached to the epidermal growth factor receptor (EGFR) mediated by the down-regulation of GALNT2 plays a critical role in the malignant phenotype of HCC cells (22). Moreover, overexpression of core 1␤-1,3-galactosyltransferase activates hepatocyte growth factor signaling in hepatocellular carcinoma (23).…”
mentioning
confidence: 99%
“…Besides, by means of ITRAQ labeled proteomics profiling study, we also found 50 dysregulated proteins in XL-2sci, some of which played an important role in tumor metastasis. For example, FSCN1 has been reported to be relevant with NSCLC metastasis, and G3V1S6 was said to be involved in the distant metastasis of breast cancer (51), gastric cancer (52) plus liver cancer (53). In addition, NDRG1 was connected with colorectal cancer and liver cancer, whereas, it was highly expressed in lung cancer.…”
Section: Discussionmentioning
confidence: 99%